Proactive employers and teachers' working time regulation: Public sector industrial conflicts in Denmark and Norway. (August 2019) - Mailand, Mikkel
Public sector industrial relations in Denmark are normally perceived as relatively consensual, and as a 'model employer' country with a strong collective bargaining tradition it is one of the countries where unilateral regulation could be least expected. However, in 2013, a lockout without any prior strike or strike-warning in the bargaining area for primary and lower secondary education only, came to an end through legislative intervention. The article includes three main arguments. First, the government and the public employers took these drastic steps because various factors created a rare 'window of opportunity' for them. Second, the reason a Norwegian industrial conflict in 2014 with a very similar point of departure ended very differently was first and foremost that the Norwegian process was not embedded in politics and policy reform to the same extent as the Danish process. Third, the Danish case shows that Denmark might not have escaped the trend towards unilateralism seen across Europe.